REKONSTRUKSI MODEL KEPUTUSAN JAMAAH BERBASIS KEPERCAYAAN DALAM INDUSTRI HAJI DAN UMROH: STUDI LITERATUR PADA PT NUR HAMDALAH PRIMA WISATA - Moch. Safri Jalla Asmoro; Jauharotina Alfadhilah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the management of Hajj and Umrah services in improving pilgrims’ satisfaction at PT NUR HAMDALAH PRIMA WISATA through a library research approach. Hajj and Umrah services are part of the religious service sector that require professional management because they are closely related to spiritual needs, comfort, and pilgrims’ trust. Increasing competition in the Hajj and Umrah travel industry requires companies to provide high-quality services in order to maintain customer satisfaction and loyalty. This study employs a qualitative descriptive method using library research. Data were collected through literature review from scientific journals, books, regulations, and previous studies relevant to service management, service quality, and pilgrims’ satisfaction. Data analysis was conducted using content analysis techniques to identify and interpret service concepts based on the SERVQUAL theory, which includes tangible, reliability, responsiveness, assurance, and empathy dimensions. The findings indicate that effective service management contributes to improving pilgrims’ satisfaction through adequate facilities, reliable services, responsive staff, assurance of safety and professionalism, and personalized attention to pilgrims’ needs. The implementation of these five dimensions of service quality can build trust, enhance loyalty, and strengthen the company’s image in the Hajj and Umrah travel industry. This study provides theoretical contributions to the development of religious service management studies and serves as a conceptual reference for travel agencies in improving service quality for pilgrims.